Economic Globalization and Postcolonial Women: A Critical Study of Monica Ali’s Brick Lane (2003) - Dr. Kalsoom Khan (University of Chitral Journal of Linguistics and Literature, 2023)
The present literary study posits the argument that Monica Ali’s novel Brick Lane (2003) delineates that global capitalist dicta such as the deregulation of economy, reduction in state responsibility and reliance upon private administration imposed upon the weaker economies of the postcolonial nation-states by global monetary organizations are highly detrimental to the economic status of women. As a result of these policies, governments reduce expenditure on public health, education, housing, and other such areas. Women’s neglected health, poor education, low paid jobs and childbirth/care liabilities make them depend greatly on these services and are extremely distressed by these cuts. The shift of industries from global North to South to procure cheap labor has resulted in employment opportunity for southern women yet exploitation far exceeds the rosy prospects. To substantiate the claim in relation to this particular strain and motif in the novel, the theoretical concepts of feminist economics, inequitable wages and sexual exploitation, from within the theory of Postcolonial Feminism, are applied in the analysis of the fictional work. Through a scrutiny of the two central female characters and variations in their economic situation in the novel, the study tries to assess women’s monetary position in relation to the global and local economic processes.